Sosialisasi Membangun Kemandirian Finansial Santri melalui Literasi Akuntansi Dasar pada Pondok Pesantren Nurmadani NW Montong Lisung - Kurniati, Mia; Putri, Tutik Sukmalasari; Sutrianingsih, Sutrianingsih (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
This community service program aims to improve the basic accounting literacy of the students (santri) at Pondok Pesantren Nurmadani NW Montong Lisung as a strategic effort to strengthen their financial independence. The program was initiated in response to the limited understanding of systematic financial management among santri, despite their involvement in various economic activities within the pesantren, such as the cooperative, canteen, and student organizations. The activities were carried out through four main stages: needs assessment, socialization of basic accounting concepts, financial record-keeping training, and evaluation accompanied by follow-up assistance. Interactive learning methods and experiential learning approaches were applied to ensure that participants not only understood theoretical concepts but were also able to practice them directly. The results showed a significant increase in the santris’ knowledge of the basic accounting equation, general journal, ledger posting, and preparation of simple financial statements. In addition to improved knowledge, there was also a positive shift in attitudes toward the importance of transparency, accountability, and sound financial governance. Several pesantren units began implementing the financial recording formats introduced during the training. Overall, this program successfully enhanced the technical skills and financial awareness of the santri and contributed to strengthening the pesantren’s financial management practices in a more professional and sustainable manner.